Near‐net‐size preparation of porous mullite matrix ceramics with in situ formed 3D mullite whisker network. Issue 6 (29th August 2022) - Yan, Hao; Chen, Shile; Lang, Ying; Wei, Hongkang; Tian, Chuanjin; Wang, Chang‐An
Abstract: Porous mullite matrix ceramics have excellent thermal and mechanical properties suitable for applications such as in thermal insulation. However, their applications are limited by processing defects from nonuniform sintering shrinkage and the trade‐off between high porosity (preferred for low thermal conductivity) and high mechanical strength. Herein, we seek to minimize the sintering shrinkage by near‐net‐size preparation and improve the strength by in situ formed whisker network structure. Gelcasting forming technology and pressureless sintering were used to prepare porous mullite matrix ceramics using kyanite and α‐Al2 O3 powders as the starting materials and using MoO3 to promote the growth of mullite whiskers. The results showed that the sintering shrinkage could be compensated by the volume expansion from solid‐state reaction during reaction sintering. The in situ formed three‐dimensional (3D) whisker network further reduced sintering shrinkage and effectively improved the strength of the ceramics. An ultralow sintering shrinkage of .78% was achieved. The near‐net‐shape porous mullite matrix ceramics strengthened by 3D whisker network had a high porosity of 63.9%, a high compressive strength of 83.8 MPa and a high flexural strength of 53.5 MPa.